THE IMPORTANCE OF ADOPTION INTERNATIONAL ACCOUNTING STANDARD (IAS 12) THE INCOME TAXES TO DRAW THE FOREIGN INVESTMENTS AND DEVELOPING THE IRAQI ECONOMY - A.P.D. Mostafa Kazemi Najaf Abadi , Jamal Noaman Mohammed (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
One of the important bases requires to attract the foreign investments is the obligation of the state and its companies to apply the International Standards in preparing its suitable financial reporting which therefore makes it trustworthy for the investors where he can read and compare it with the economic activities for the same sector, or with the last years, and with other international companies in addition to the attaining the sufficient disclosure and the requisite transparency. In closing, the research will come up within important conclusion which is the necessity to depend on the International Standard No. (12) for income taxes in drafting the accounting policies which have to be followed in Iraq local environment. Since the unified accounting system applied in Iraq has become old, and restricted within the Iraqi environment only, where it came to serve the objectives which have become limited and old due to the changes taken place inside and outside the environment of the country, consequently, it does not assist in its current status to attract the foreign investments which therefore requires its adjustment and this is what the research is aiming at